La filosofía nosótrica andina y la justicia indígena en el estado ecuatoriano - Mora Cárdenas, Doris Mariela (2025)
The nosotric philosophy from the Indigenous cosmovision promotes a holistic vision of being and the environment, emphasizing collectivity and interconnectedness among all the elements of the universe placing the human being as a part of this universe as energy. In the Ecuadorian context, this philosophy is manifested in justice practices that seek to restore community harmony and the natural balance. Indigenous justice, based on nosotric principles such as reciprocity and the complementarity are distinguished by its restorative approach. Through symbolic rituals that involve natural and spiritual elements, it seeks reconciliation and the reintegration of the individual into the community. The ultimate objective is to restore the community harmony and strengthen social bonds. Indigenous justice recognizes the interdependence between human beings and their environment. Nature is a fundamental element in the healing and restorative processes. For example, the use of water in rituals symbolizes the purification and renewal, while the whippings represent repentance and atonement. The 2008 Ecuadorian Constitution recognizes the indigenous justice and its application within the legal framework of the State. However, the implementation of this pluralistic legal system faces challenges such as lack of mutual comprehension between the Indigenous and State legal systems. Cooperation and intercultural dialogue are fundamental to overcome these obstacles and build an equitable legal system that respects cultural diversity. The Andean nosotric philosophy offers a unique perspective on the justice emphasizing the importance of the community, nature, and spirituality. Indigenous justice, once it has been recognized by the Constitution, represents a significant progress toward inclusion and respect to cultural diversity in Ecuador. However, it is necessary to continue working to guarantee the effective implementation of this pluralistic legal system and to overcome the challenges that persist, starting from the Indigenous understanding and empowerment over the Westernization.